Presentación - Bernal Zuluaga, Hernando Alberto (Poiésis, 2020)
The members of magazine Poiésis makes known to the readers the issue No. 39, edition with which this one reaches its 20 years. Indeed, the digital magazine Poiésis is celebrating its birthday and not a few. It has been 20 years of utopias, determined work, and perseverance, a work from which something new is learned every day. The editorial carried out by Master Edison Francisco Viveros Chavarría, professor at the Luis Amigó Catholic University in the Family Program, and professor at the University of Antioquia, in which he is also training as a philosopher. In this editorial, Viveros presents us with a personal story, which happened at the University of A. with its students, related to the times of the Pandemic that we are suffering, and that invites us to reflect on the importance of offering hospitality to all those who around us.